Pulse 2 : report on a phenomenon - Cole, Herbert M.; Doll, Nancy; Plous, Phyllis; Ruiz, Raúl; Shamash, Diane; Torrent, Jodi (Santa Barbara : University Art Museum, 1990)
Aycock, Alice ; Barry, Steve ; Baschet, Bernard & François ; Bell, Bill ; Bertoia, Harry ; Borofsky, Jonathan ; Boto, Martha ; Brener, Roland ; Buchen, Bill & Mary ; Calder, Alexander ; Clark, James O. ; Cortright, Steven ; Dollhausen, Jack ; Duchamp, Marcel ; Dunlap, Richard ; Fischer, R.M. ; Riverhead (New York) ; Fontana, Bill ; Garrard, Mimi & Seawright, James ; Hardesty, Michael ; Hayden, Michael ; Holzer, Jenny ; Horn, Rebecca ; Irwin, Robert ; Jones, Howard ; Jones, Joe ; Jones, Kristin & Ginzel, Andrew ; Kessler, Jon ; Komisar, Milton ; Lehr, Harold ; Lewis, Evan ; Lye, Len ; Lynds, Clyde ; Mack, Heinz ; Mahler, David ; Mallory, Ronald ; Moholy-Nagy, Laszlo ; Nauman, Bruce ; Okamoto, Rikuro ; Oppenheim, Dennis ; Orr, Eric ; Paik, Nam June ; Parc, Julio Le ; Phillips, Liz ; Rath, Alan ; Rhoads, George ; Rickey, George ; Ruiz, Raoul ; Seawright, James ; Siña, Alejandro & Moira ; Soto, Jesus Rafael ; Spellings, Art ; Survival Research Laboratories ; Takis ; Tinguely, Jean ; Victoria, Ted ; Vogel, Peter
Exhibitions Frequently Cited, Selected Reading List p. 72-75
biog. per kunstenaar
Pulse 2 : report on a phenomenon, Exhibition Locations: Pulse 2: University Art Museum, Santa Barbara, 7 July - 21 October 1990 ; College of Creative Studies Gallery, 7 July - 5 October 1990 ; University Center Gallery, 7 July - 26 October 1990
Engels
boek